PENGUATAN NILAI AGAMA DAN PENDIDIKAN MORAL REMAJA MELALUI IMPLEMENTASI HOME VISIT DALAM PROGRAM BIMBINGAN KONSELING ISLAM - Dirman - Dirman (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2022)
Education aims to improve not only children intellectuality and skill, but also build moral and ethical values of the children. This research was conducted to reveal the planning, implementation and evaluation of home visits as a counseling program with an Islamic perspecetive and at SMK Cut Nyak Dien Semarang City. The objectives of this study are to determine the planning, implementation and evaluation of home visits as an Islamic counseling program. This research was using a descriptive qualitative approach. The data is collected through a several process ofÂ collecting data such as observation techniques, interviews and documentation. The results of this study indicate that the implementation of the home visit with an Islamic counseling guidance program is appropriate. This success was influenced by the planning, implementation and evaluation carried out by the teacher which is in accordance with the standard home visit operational procedures and in accordance with the Islamic guidance and counseling function.Keywords: Home visit, Islamic Counseling, Teacher Counseling